Gender-specific differences in outcome of ascending aortic aneurysm surgery - Beller, Carsten J.; Farag, Mina; Wannaku, Sepali; Seppelt, Philipp; Arif, Rawa; Ruhparwar, Arjang; Karck, Matthias; Weymann, Alexander; Kallenbach, Klaus (PLOS ONE, 2015)
Objectives Gender specific differences receive increasing attention and are known to affect the outcome of cardiovascular diseases. We investigated possible risk-factors for gender-specific differences in ascending aortic aneurysm surgery. Methods 548 consecutive patients (male: n = 390, age: 58.3±14.4 years; female: n = 158, age: 65.3±12.9 years) with aneurysms of the ascending aorta eligible for cardiac surgery were retrospectively analyzed. Results Women were significantly older when operation was indicated (p<0.001) and presented with significantly more hypertension (p=0.04) and chronic obstructive pulmonary disease (COPD; p = 0.017), whereas men had significantly more previous cardiac operations (p = 0.016). Normalized aortic diameters (diameter / body surface area) were significantly larger in women (3.10±0.6 cm) vs. (2.75±0,5 cm, p≤0.001) in men, without differences in absolute values (5.74±1.04 cm vs. 5.86±1.34 cm). The aortic arch was significantly more involved in aneurysm formation in women (p = 0.04). Follow-up was available in 93% of the patients with a mean follow-up time of 3.9±3.9 (0-17.8) years. 30-day mortality was 3.5% in men (n=12) and 7.9% in women (n=11; p = 0.058). Univariate regression analysis shows gender specific risk factors for 30-day mortality in men to be age: p = 0.028; myocardial infarction: p = 0.0.24 and in women diameter of the ascending aorta: p=0.014; renal insufficiency: p=0.007. Long-term survival was significantly reduced in women (log-rank p = 0.0052). Conclusions The outcome after surgery for ascending aortic aneurysm is less favourable in women with significantly reduced long-term survival and a trend to increased 30-day mortality in this cohort. Larger normalized aortic diameters, higher incidence of involvement of the aortic arch and differences in comorbidities may contribute to gender differences. Women undergo surgery at higher age and more progressed state of aortic disease. Therefore, gender-specific guidelines for ascending replacement may be useful to improve outcome in women.